Proteomic and probit analyses of glufosinate-ammonium-resistant goosegrass(Eleusine indica (L.) Gaertn.) biotypes in Malaysia / Adam bin Jalaludin - Jalaludin, Adam (2011)
Goosegrass (Eleusine indica [L.] Gaertn.), regarded as one of the world’s worst weeds is highly pernicious to cash crop growers in Malaysia. Following reports in 2009 that glufosinate ammonium failed to adequately control goosegrass populations in Kesang, Malacca and Jerantut, Pahang, Malaysia, on-site field trials were conducted to assess the efficacy of glufosinate-ammonium and glyphosate towards goosegrass from both places. Glufosinate-ammonium at 495 g ai ha1 managed to provide 82% control of the weed at the vegetable farm while the same rate failed to control goosegrass at the oil palm nursery. Glyphosate failed in controlling goosegrass population at both places where the highest rate (4320 g ae ha-1) produced 13% and 3% control, respectively. The efficacy of both herbicides was also tested on the Kesang and Jerantut goosegrass grown from seeds. Glufosinate-ammonium at the recommended rate provided satisfactory control of the Kesang biotype while the same rate failed to control Jerantut biotype. Glyphosate at 540 g ae ha-1 again failed in damaging both biotypes. The highest rate used managed to control the Kesang biotype but still did not effectively damage the Jerantut biotype. Comparison with susceptible goosegrass showed that the ‘Kesang’ biotype was 1 and 6-fold more resistant to glyphosate and glufosinateammonium respectively while the ‘Jerantut’ biotype was 3- and 30-fold more resistant to glyphosate and glufosinate-ammonium respectively. The low glyphosate resistance index (R.I) value for both biotypes were believed to be caused by the significant tolerance of the susceptible biotype against glyphosate. Proteomic analysis was conducted to see any differences in the proteins expressed by the susceptible, the Kesang and the Jerantut biotypes. There were 150 matched spots between the susceptible and the Jerantut biotypes, with 4 spots differentially expressed. Between the susceptible and the Kesang biotypes, a total of 145 spots were matched, but only 3 spots were differentially expressed. Most of the differences in abundance were due to the presence or absence of a protein in either the susceptible or the Jerantut and Kesang biotypes. MALDI-TOF analysis successfully identified the identities of ten spots from the Jerantut biotype proteome. They include peptidyl-prolyl cis-trans isomerase, ferredoxin NADP+ reductase, peroxiredoxin, granule bound starch synthase, WD-repeat protein and a small subunit of RuBisCO. The remaining four proteins were unknown and hypothetical proteins. The functions of these protein ranges from folding of proteins, electron transfer, storage, DNA and RNA related processes, antioxidants and even stress-related functions. The occurrence of glufosinate-ammonium resistance in goosegrass calls for more research to better understand the resistance mechanism of this particular weed and more integrated management of the weed to prevent escalating resistance and further proliferation in the country.